1955
DOI: 10.1104/pp.30.1.33
|View full text |Cite
|
Sign up to set email alerts
|

Free Auxins and Free Tryptophane in the Strawberry.

Abstract: It has been previously demonstrated (15) that the growth of the strawberry receptacle is regulated by the achenes. This control is exerted through substances which are active in the Avena test, a standard test for auxins. The exact identity of these natural auxins, however, had not been investigated. The purpose of this paper is to report further experiments on the production of auxins by strawberry achenes, on the level of free tryptophane, a generally presumed raw material in the genesis of natural indolic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
56
1
5

Year Published

1956
1956
1998
1998

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 117 publications
(69 citation statements)
references
References 21 publications
6
56
1
5
Order By: Relevance
“…Genesee used b-Powell (27) was tried and found to elongate very much at IAA concentrations superior or equal to 10 ugm,/l, especially when the sections were soaked in water prior to the actual assay (see below, section 6). As far as oats are concerned, the problem of dehusking thousands of seeds had been solved previously by using hulless varieties, such as Brighton (25). The first internodes of this variety 1,000 3.52…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Genesee used b-Powell (27) was tried and found to elongate very much at IAA concentrations superior or equal to 10 ugm,/l, especially when the sections were soaked in water prior to the actual assay (see below, section 6). As far as oats are concerned, the problem of dehusking thousands of seeds had been solved previously by using hulless varieties, such as Brighton (25). The first internodes of this variety 1,000 3.52…”
mentioning
confidence: 99%
“…Studies of this type on isolated animal mitochondria (25) have revealed a characteristic electron pathway from pyridine nucleotide to flavin, thence via an un-…”
mentioning
confidence: 99%
“…It seems safe to assume, then, that any of the simple 836 neutral indoles can be quantitatively transferred to acetonitrile from hexane with 2 or 3 extractions. This step is convenient for separating many lipids from the neutral indoles (8). The basic indoles tryptamine, gramine, and bufotenine were converted from their salts to the free bases by 1 N NH4OH, thus enabling them to be partitioned from 1 N NH4OH into methylene chloride.…”
Section: Resultsmentioning
confidence: 99%
“…Column, 8.0 g of silica gel hydrated with 5.0 ml of 0.5 M formic acid; fraction size, 5.4 ml; solvents, Varigrad chamber no. 1-100 ml n-hexane saturated with 0.5 M formic acid; Varigrad chamber no.…”
Section: Resultsmentioning
confidence: 99%
“…Indoleacetic acid (IAA) is probably the active principle responsible for the growth of strawberry receptacles (14). The biosynthesis of this compound has been studied and demonstrated in many plants and plant parts (3).…”
mentioning
confidence: 99%